An IIoT based secure and sustainable smart supply chain system using sensor networks. Issue 2 (9th November 2022) - Singh, Samayveer; Kumar, Mohit; Verma, Om Prakash; Kumar, Rajeev; Gill, Sukhpal Singh
Abstract: Industrial Internet of Things (IIoT) is a very effective and efficient way to track products during their production, packaging, storage, and shipments. It can also help in monitoring their real‐time conditions such as location, speed of moments, and temperature. Presently most of the supply chain management systems are not effective due to their inefficient tracking of real‐time shipments, long delays in shipments and lost identification on a real‐time basis, and uneconomical storage of goods. To solve these problems, an IoT‐based secure and sustainable smart supply chain system using sensor networks is proposed that provides real‐time shipment tracking, storage, delay, and lost identification. Threshold‐based weighted probability formula is devised by considering the average distance and node spacing of sensor nodes, total network energy, residual, and maximum energy parameters to alleviate the hot spot problem. Additionally, the communication signals are transmitted in compression form with end‐to‐end encryption that reduces the use of bandwidth by decreasing the signal size. The percentage increment in the stability and the network lifespan of the proposed method is 35.19% and 7.23% & 119.33% and 71.72% as compared to the T. Senthil et al method and S. Singh's method, respectively. Abstract : An IIoT‐based secure and sustainable smart supply chain system using sensor networks is proposed which provides current information of the shipment, storage, delay, and lost identification on a real‐time basis. A threshold‐based weighted probability correlation formula is developed to alleviate the hot spot problem of energy consumption in the supply chain system. All the communication signals are end‐to‐end encrypted during transmitting/receiving by IoT devices in the whole supply chain system. The performance of the proposed supply chain method is evaluated with the existing method.